Integration of amorphous ferromagnetic oxides with multiferroic materials for room temperature magnetoelectric spintronics - Taz, Humaira (Sci Rep, 2020)
A room temperature amorphous ferromagnetic oxide semiconductor can substantially reduce the cost and complexity associated with utilizing crystalline materials for spintronic devices. We report a new material (Fe(0.66)Dy(0.24)Tb(0.1))(3)O(7-x) (FDTO), which shows semiconducting behavior with reasonable electrical conductivity (~500 mOhm-cm), an optical band-gap (2.4 eV), and a large enough magnetic moment (~200 emu/cc), all of which can be tuned by varying the oxygen content during deposition. Magnetoelectric devices were made by integrating ultrathin FDTO with multiferroic BiFeO(3). A strong enhancement in the magnetic coercive field of FDTO grown on BiFeO(3) validated a large exchange coupling between them. Additionally, FDTO served as an excellent top electrode for ferroelectric switching in BiFeO(3) with no sign of degradation after ~10(10) switching cycles. RT magneto-electric coupling was demonstrated by modulating the resistance states of spin-valve structures using electric fields.